Long-Term Angiotensin II Infusion Induces Oxidative and Endoplasmic Reticulum Stress and Modulates Na+ Transporters Through the Nephron - Lins, Bruna Bezerra; Casare, Fernando Augusto Malavazzi; Fontenele, Flávia Ferreira; Gonçalves, Guilherme Lopes; Oliveira-Souza, Maria (Frontiers in Physiology, 2021)
High plasma angiotensin II (Ang II) levels are related to many diseases, including hypertension and chronic kidney diseases (CKDs). Here, we investigated the relationship among prolonged Ang II infusion/AT1 receptor (AT1R) activation, oxidative stress and endoplasmic reticulum (ER) stress in kidney tissue. In addition, we explored the chronic effects of Ang II on tubular Na+ transport mechanisms. Male Wistar rats were subjected to sham surgery as a control or prolonged Ang II treatment (200 ng∙kg-1∙min-1, 42 days) with or without losartan (10 mg∙kg-1∙day-1) for 14 days. Ang II/AT1R induced hypertension with a systolic blood pressure of 173.0 ± 20 mmHg (mmHg, n = 9) compared with 108.0 ± 7 mmHg (mmHg, n = 7) in sham animals. Under these conditions, gene and protein expression levels were evaluated. Prolonged Ang II administration/AT1R activation induced oxidative stress and ER stress with increased Nox2, Nox4, p22phox and p47phox mRNA expression, phosphorylated PERK and eIF2α protein expression as well as ATF4 mRNA expression. Ang II/AT1R also raised IL-1β, NF- kappa B and αSMA mRNA expression, suggesting proinflammatory and profibrotic effects. Regarding Na+ tubular handling, Ang II/AT1R enhanced cortical nonphosphorylated and phospho/S552/NHE3, NHE1, ENaC β, NKCC2 and NCC protein expression. Our results also highlight the therapeutic potential of losartan, which goes beyond the antihypertensive effect, playing an important role in kidney tissue. This treatment reduced oxidative stress and ER stress signals and recovered relevant parameters of the maintenance of renal function, preventing the progression of Ang II-induced CKD.